STABILITY AND ADAPTABILITY OF KERNEL CAROTENOIDS IN MAIZE - SWETA DOSAD; N. K. SINGH (The Bioscan, 2014)
The study was conducted to investigate the adaptability and stability of kernel carotenoids (KC) and grain yield in 34 maize genotypes under various locations and to determine the relation between KC and grain yield, and between kernel colour and carotenoids content. Analysis of variance indicated significant genetic variance among the test materials for grain yield and kernel carotenoids. Results showed that none of the genotypes possessed general stability criteria either for the KC or grain yield. However, the germplasm identified to be promising for grain yield were ‘PML-23’, ‘PML-10’, ‘PML-17’, ‘PML-11’, ‘PML-20’ and ‘PML-22’ whereas ‘PML-7’, ‘PML-3’, ‘PML-27’, ‘PML-31’ and ‘PML-29’ were identified to be the five promising landraces for KC. On the other hand, PML-1, PML-6, PML-17, PML-27, PML-31 were found to be promising for both the traits and may serve as potential donor particularly for improvement of carotenoids in maize hybrids or composites. Relation between KC and grain yield emerged as non-significant with very low coefficient of determination. Similarly, kernel colour was found to be associated non-significantly with KC with low coefficient of determination. The present investigation also revealed that selection based on kernel colour is not reliable for selecting lines with higher carotenoids content.